New records of demosponges (Porifera) from the South Orkney Islands (Antarctica) with a checklist for the region - Schejter, L.; Cristobo, J.; Ríos, P. (Zootaxa, 2024)
The South Orkney Islands (SOI) is a poorly studied Antarctic archipelago located in the Scotia Arc. In this study, we added 25 Demospongiae species to the SOI known sponge richness, which was previously represented by only 16 species. Of these, 22 species represent new records for SOI region, although they were previously recorded from other Antarctic sectors. Samples were collected during two Argentinean Antarctic Research Cruises onboard RV Puerto Deseado. The most frequently collected species were Artemisina apollinis, Iophon gaussi, I. unicorne, Lissodendoryx (E.) ramilobosa, Myxodoryx hanitschi and Tedania (T.) tantula. Data and illustrations of some rare or uncommon species are provided: Iophon gaussi, Lissodendoryx (E.) anacantha, Microxina charcoti, Raspailia (H.) hentscheli, Haliclona spongiosissima, Haliclona (G.) cf. cucurbitiformis. Although the present results increase substantially the previously known information on sponge species, this is still an underestimation of total richness because certain orders (Tetractinellida, Suberitida, Biemnida, Polymastiida) and classes were not studied during the current investigation, although previous records were included.